Inhibition of granulocyte elastase activity by caffeic acid derivatives - Melzig, Matthias F. (1999)
In former studies it was shown that bornyl derivates may contribute to the anti-inflamatory activity of some drugs, such as Verbesia turbacensis, Notopterygium incisum or Coreopsis mutica.